Seletividade de produtos naturais comerciais a Telenomus podisi Ashmead 1893 (Hymenoptera: Platygastridae) - Battisti, Lucas (2017)
The egg parasitoid Telenomus podisi Ashmead 1893 (Hymenoptera: Platygastridae) has been emerged as a natural enemy of the Pentatomidae family stink bug, mainly in organic agriculture, and is often used associated with natural commercial products. The use of these products may adversely affect the biological parameters of the parasitoid, which makes studies on selectivity to the natural enemies extremely important for the appropriate management of the insect pests. Therefore, the objective of this study was to evaluate the selectivity of natural commercial products to T. podisi in laboratory conditions. For this, four bioassays were performed: 1-free choice test; 2- no choice test pre-parasitism; 3-no choice test post-parasitism and 4-Test on adults of T. podisi. The products tested were Azamax®, Orobor®, Difere® (bioassays 1, 2 e 3), Metarril® and Boveril® (all bioassays), used at the concentration recommended by manufacturer. The percentage of parasitism, emergency percentage, sex ratio, eggadult period and longevity were the parameters evaluated. It was observed that the product Azamax® reduced the parasitism of T. podisi in the three tests performed (1, 2 and 3), being considered non-selective to this parasitoid. The other products did not change most of the evaluated parameters, mainly the parasitism (pre and post parasitism) and the sex ratio, being considered selective to T. podisi. In bioassays 4, regarding to the Metarril® and Boveril® products, these changed only in the percentage of emergence and longevity of adult females parameters. Orobor®, Difere®, Metarril® and Boveril® are considered selective to T. podisi whereas the Azamax® product was not selective.